Disruption of artificial lipid bilayers in the presence of transition metal oxide and rare earth metal oxide nanoparticles. (15th November 2018) - Acharya, Shiv; Lu, Bin; Edwards, Shayson; Toh, Christopher; Petersen, Andre; Yong, Chentao; Lyu, Peipei; Huang, Anderson; Schmidt, Jacob
Abstract: The unique properties of nanoparticles have made them popular materials for a wide variety of applications. Their prevalence has increased research attention to their potential toxicity, and multiple groups have found that certain nanoparticles are biologically hazardous and can induce autophagy, oxidative stress, nucleic acid damage, and cell membrane damage. In particular, multiple studies have investigated interactions between nanoparticles and cell membranes. Here, we use a high throughput artificial lipid bilayer platform capable of high resolution electrical measurements of bilayer conductance to screen for interaction between lipid bilayers and metal oxide and rare earth metal oxide nanoparticles 15–200 nm in diameter composed of: Fe3 O4, Eu2 O3, Er2 O3, Co3 O4, ZnO, La2 O3, Gd2 O3, CeO2, In2 O3, CuO, HfO2, and TiO2 . We found that all particles, with the exception of Fe3 O4, TiO2, and HfO2, exhibited significant interactions with lipid bilayers, causing them to rupture a short time after addition to the solution adjacent to the bilayer. We measured this at several pH values and ionic strengths, finding, in agreement with prior work, that cationic nanoparticle surface charge correlated strongly with nanoparticle-induced disruption of lipid bilayers.